Silk fibroin-based adhesive patch for tissue wound suture-free repair and preparation method of silk fibroin-based adhesive patch

Through the two-layer structure of silk fibroin-based adhesive patch, combined with the cross-linking technology of hydrogel matrix layer and adhesive layer, the existing suture technology consumes time and local stress concentration problems are solved, and strong mechanical toughness and wetness are achieved State adhesion performance is suitable for seamless repair of soft tissues, and has good biocompatibility and degradability.

CN119236154AActive Publication Date: 2025-01-03FUZHOU UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411626784.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-01-03
Estimated Expiration
2044-11-14

Smart Images

  • Figure CN119236154A_ABST
    Figure CN119236154A_ABST
Patent Text Reader

Abstract

The invention discloses a silk fibroin-based adhesive patch for tissue wound suture-free repair and a preparation method of the silk fibroin-based adhesive patch. The patch is composed of two layers, and the two layers are tightly combined. The first layer is a high-toughness hydrogel matrix layer and is formed by cross-linking methacrylic acid esterification modified silk fibroin and acrylamide, and second network sodium alginate-calcium ions are added; and the second layer is a bonding layer with strong adhesion performance and is formed by self-assembly crosslinking of silk fibroin, polyethylene glycol and tannic acid. The silk fibroin-based bonding patch prepared by the invention has the advantages of excellent mechanical toughness, wet adhesion sealing performance, biodegradability, biocompatibility and promotion of suture-free repair of tissues. The adhesive patch is convenient to use and high in portability, can be self-adhered to a target tissue interface, is prevented from diffusing and permeating to a non-injury part, and has a wide application prospect in the aspect of soft tissue injury repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biomedical material preparation, and in particular relates to a silk fibroin-based adhesive patch for sutureless repair of tissue trauma and a preparation method thereof. Background Art

[0002] Uncontrolled bleeding during surgery or trauma is one of the leading causes of death in the world today. Trauma to internal soft tissues, especially gastrointestinal perforation, peripheral nerve defects, and visceral bleeding, can lead to serious life-threatening symptoms. For example, gastrointestinal perforation can cause leakage of liquid contents, acute peritonitis and sepsis, and even death; severe peripheral nerve damage can even lead to paralysis and permanent disability. Traditionally, surgical suturing is often used as a standard technique for connecting or closing wound tissues. However, in clinical practice, surgical suturing still has inherent disadvantages, such as long time consumption and high surgical skill requirements. Especially when used for the closure of gastrointestinal defects, this suture has a high risk of leaking body fluids / air from the treated gastrointestinal tissue, leading to serious infection or even death. More seriously, surgical suturing causes secondary damage and local stress concentration to surrounding tissues. Therefore, the innovation of developing clinical alternative materials to replace sutures is not only aimed at preventing liquid / air leakage, but also reducing local stress concentration and irreversible damage at the target wound.

[0003] In order to solve the problems existing in suturing, tissue adhesive patches have been widely developed. Adhesive patches have outstanding features such as easy use and simple operation. Tissue adhesive patches can adaptively fit biological tissues and form interfacial adhesion with tissues to promote wound repair. In order to address the above problems, the development of tissue adhesive patches with strong wet adhesion, excellent mechanical toughness and biodegradability has received increasing attention and is expected to solve the problems existing in existing repair methods.

[0004] Silk fibroin is a biocompatible and biodegradable material with excellent physical properties. It is widely used in the fields of biomaterials, tissue engineering, regenerative medicine or medical equipment. At present, most of the silk fibroin-based patches on the market are microneedle patches. For example, Qi Zhenzhen et al., whose publication number is CN113679657A, developed a silk fibroin microneedle transdermal patch for treating insomnia; Lu Shenzhou et al., whose publication number is CN117838841A, developed a silk fibroin insulin microneedle patch. However, the above-mentioned patches are slightly insufficient in terms of mechanical toughness and wet adhesion performance. Therefore, it is urgent to develop a silk fibroin-based patch material with strong toughness and strong wet adhesion. Summary of the invention

[0005] The purpose of the present invention is to provide a tissue adhesive patch with excellent mechanical toughness, wet adhesion, biodegradability, biocompatibility and facilitating sutureless repair of tissues in view of the deficiencies of the prior art. The present invention overcomes the problems of the existing suture materials in that the wound treatment is time-consuming, the skill requirements are high, the secondary damage is easily caused, and the clogging after surgery is caused. The prepared silk fibroin-based adhesive patch material for sutureless repair of tissue trauma can be used for healing and repairing soft tissue wounds, and has a wide range of application prospects in the sutureless repair of various soft tissues.

[0006] To achieve the above object, the present invention adopts the following technical solution: A method for preparing a silk fibroin-based adhesive patch for sutureless repair of tissue trauma, wherein the patch consists of two layers, the first layer is a hydrogel matrix layer formed by cross-linking methacrylated silk fibroin with acrylamide, and sodium alginate and calcium ions are added; the second layer is an adhesive layer formed by self-assembly cross-linking of silk fibroin, polyethylene glycol and tannic acid.

[0007] The above-mentioned method for preparing a silk fibroin-based adhesive patch for sutureless repair of tissue trauma specifically comprises the following steps: (1) Preparation of hydrogel matrix layer: Add acrylamide aqueous solution to the methacrylated silk fibroin solution and stir evenly, then add sodium alginate aqueous solution, calcium sulfate dihydrate and photoinitiator and mix well to obtain a hydrogel matrix layer precursor solution, pour the precursor solution into a mold and place it in a dark box, and irradiate with ultraviolet light for 10 minutes to form a hydrogel matrix layer; (2) Preparation of adhesive layer powder: The silk fibroin solution and the polyethylene glycol aqueous solution are mixed, and an equal volume of tannic acid aqueous solution is added, and stirred to obtain a solid colloidal substance. The solid colloidal substance is freeze-dried, ground, and sieved to obtain an adhesive layer powder; (3) Preparation of a silk fibroin-based adhesive patch: coating the adhesive layer powder obtained in step (2) on the hydrogel matrix layer obtained in step (1), and placing the mixture in a constant temperature and humidity incubator to obtain a silk fibroin-based adhesive patch; the temperature in the constant temperature and humidity incubator is 35°C-38°C, and the relative humidity is 50%-60%.

[0008] Furthermore, the preparation method of the methacrylated silk fibroin in step (1) is to dissolve the degummed silk with lithium bromide to obtain a silk fibroin solution, then add glycidyl methacrylate, stir for 3 hours in a dark place, then dialyze with deionized water for 5-7 days, centrifuge, and take the supernatant to obtain a methacrylated silk fibroin solution, wherein the mass fraction of the methacrylated silk fibroin solution is 0.1% - 5%.

[0009] Furthermore, in step (1), the mass fraction of the acrylamide aqueous solution is 10%-50%, the mass fraction of the sodium alginate aqueous solution is 1%-5%, the molar concentration of the calcium sulfate dihydrate is 0.1M-1M; and the molar concentration of the photoinitiator is 0.001M-0.1M.

[0010] Furthermore, the photoinitiator in step (1) is lithium phenyl-2,4,6-trimethylbenzoylphosphinate or α-ketoglutaric acid.

[0011] Furthermore, the preparation method of the silk fibroin solution in step (2) is to dissolve the degummed silk with lithium bromide, then dialyze with deionized water for 1-3 days, and centrifuge to obtain the silk fibroin solution; the mass fraction of the silk fibroin solution is 1%-10%.

[0012] Furthermore, the polyethylene glycol in step (2) is one of polyethylene glycol 500, polyethylene glycol 1000 and polyethylene glycol 2000; and the mass fraction of the polyethylene glycol aqueous solution is 1%-5%.

[0013] Furthermore, in step (2), the volume ratio of the silk fibroin solution to the polyethylene glycol aqueous solution is 5:1-1:5; and the mass fraction of the tannic acid solution is 10%-30%.

[0014] Furthermore, the standing time in step (3) is 1-20 minutes.

[0015] A silk fibroin-based adhesive patch prepared by the preparation method and used for sutureless repair of tissue trauma.

[0016] The beneficial effects of the present invention are: (1) The tissue adhesive patch prepared by the present invention has a two-layer structure, in which the hydrogel matrix layer has strong mechanical toughness. On the basis of methacrylate-modified silk fibroin, acrylamide, sodium alginate, calcium sulfate dihydrate and photoinitiator are added to synthesize the hydrogel matrix layer. The tough hydrogel matrix layer utilizes the covalent cross-linking between methacrylate-modified silk fibroin and acrylamide to maintain elasticity, and utilizes sodium alginate / calcium ion cross-linking as a recoverable sacrificial bond to effectively dissipate energy, giving the gel excellent mechanical toughness to adapt to dynamic physiological movement. The tensile elongation of the patch material of the present invention is more than 200%, and the toughness strength is 400 KJ / m 3 above.

[0017] (2) The adhesive patch of the present invention has strong wet tissue adhesion properties. The adhesive layer is self-assembled and cross-linked by silk fibroin solution, polyethylene glycol solution and tannic acid solution. The polyphenol structure contained in tannic acid can bond with functional groups such as amide bonds, amino groups, and thiol groups in tissue surface proteins, thereby giving the adhesive patch strong adhesion ability on the tissue surface; and the double-layer structure makes the patch material of the present invention have excellent mechanical toughness and strong wet adhesion properties, and proves that it has broad application prospects in the adhesion and sealing of soft tissue injuries such as the gastrointestinal tract. The in-situ bonding characteristics of the patch material of the present invention also provide more convenience for application.

[0018] (3) The raw materials of the present invention have good biocompatibility and degradability.

[0019] (4) The present invention has the advantages of simple operation and ease of mass production, and has good industrialization prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 : Adhesion strength of silk fibroin-based adhesive patches in wet environment.

[0021] Figure 2 : Adhesion strength of silk fibroin-based adhesive patches on different tissues.

[0022] Figure 3 : Comparison of the adhesion strength of silk fibroin-based adhesive patches and commercial adhesives to fresh porcine skin.

[0023] Figure 4 : The in vitro sealing effect of silk fibroin-based adhesive patch on different tissues. DETAILED DESCRIPTION

[0024] The technical solution of the present invention is further described below in conjunction with specific implementation methods, but the application of the present invention is not limited thereto.

[0025] Example 1 This embodiment discloses a method for preparing a silk fibroin solution, and the specific steps are as follows: After 2 L of deionized water was heated to boiling, 8.48 g of anhydrous sodium carbonate was added. After it was fully dissolved, 20 g of silkworm silk was added for degumming for 30 minutes to obtain degummed silk. The degummed silk was taken out and washed with deionized water, dried in an oven at 65°C, and the dried degummed silk was added to 50 mL of lithium bromide solution (9.3M), dissolved at 65°C for 3 hours to obtain a mixed solution. The mixed solution was poured into a dialysis bag with a molecular weight cutoff of 3500 Da and dialyzed with deionized water for 3 days. After the dialysis was completed, the solution was centrifuged at 4°C and 9000 rpm for 20 minutes, the precipitate was discarded, and the supernatant was collected to obtain the silk fibroin solution, which was placed in a refrigerator at 4°C and kept away from light for later use.

[0026] Example 2 This embodiment discloses a method for preparing a methacrylate-modified silk fibroin solution, and the specific steps are as follows: After 3 L of deionized water was heated to boiling, 15.9 g of anhydrous sodium carbonate was added. After it was completely dissolved, 120 g of silkworm silk was added for degumming for 60 minutes to obtain degummed silk. The degummed silk was fully washed with deionized water and dried in an oven at 65°C. Subsequently, the degummed silk was added to 200 mL of lithium bromide solution (9.3M) and dissolved at 65°C for 1 hour. Subsequently, 12 mL of glycidyl methacrylate was added and reacted at 60°C for 3 hours. The reaction process was protected from light. The reacted solution was poured into a dialysis bag with a molecular weight cutoff of 8000-14000Da and dialyzed with deionized water for 6 days. After the dialysis was completed, the solution was centrifuged at 4°C and 9000 rpm for 20 minutes, the precipitate was discarded, and the supernatant was collected to obtain the methacrylate-modified silk protein solution, which was placed in a refrigerator at 4°C and protected from light for later use.

[0027] Example 3 This embodiment discloses a method for preparing a silk fibroin-based adhesive patch for sutureless repair of tissue trauma, and the specific steps are as follows: (1) Preparation of hydrogel matrix layer: Mix 1% by mass methacrylate-modified silk fibroin solution and 30% by mass acrylamide solution, stir evenly, then add 2% by mass sodium alginate aqueous solution, 0.75 M calcium sulfate dihydrate and 0.075 M α-ketoglutaric acid and mix well to obtain a hydrogel matrix layer precursor solution. Pour the precursor solution into a mold and place it in a dark box. Irradiate with 365 nm ultraviolet light for 10 minutes to form a gel to obtain a hydrogel matrix layer.

[0028] (2) Preparation of adhesive layer powder: Mix 5% silk fibroin solution and 2% polyethylene glycol aqueous solution in a volume ratio of 1:1, then add an equal volume of 20% tannic acid aqueous solution and mix well. Discard the liquid portion, freeze-dry the solid colloidal substance at -80°C, grind it, and sieve it through a 200-mesh sieve to obtain the adhesive layer powder.

[0029] (3) Preparation of silk fibroin-based adhesive patch: The adhesive layer powder prepared above is coated on the hydrogel matrix layer, and the temperature of the constant temperature and humidity incubator is set to 37°C and the relative humidity is set to 60%. After standing for 5 minutes, a silk fibroin-based adhesive patch is obtained.

[0030] The tensile elongation of the silk fibroin-based adhesive patch in this embodiment is 210%, and the toughness strength is 460 KJ / m 3 The adhesion strength in the blood environment is 653.31 J / m2 (See Figure 1 ); Silk fibroin-based adhesive patches have high adhesion strength to different tissues (muscle, skin, stomach, intestine) (see Figure 2 ). The above results fully demonstrate that the silk fibroin-based patch has excellent wet tissue adhesion properties. Compared with fresh pig skin, the adhesion strength of commercially available adhesives (3M-Tegaderm Hydrocolloid (Tegaderm), cyanoacrylate (Histoacryl) and 3M-Steri-Strip (3M-SS)) is lower than that of the adhesive patch of the present invention (see Figure 3 ). Through the sealing experiment of different tissues in vitro (pig intestine, pig stomach, pig lung), it was shown that the silk fibroin-based patch has excellent tissue sealing performance in a wet environment (see Figure 4 ).

[0031] Example 4 This embodiment discloses a method for preparing a silk fibroin-based adhesive patch for sutureless repair of tissue trauma, and the specific steps are as follows (1) Preparation of hydrogel matrix layer: Mix 2% by mass of methacrylate-modified silk fibroin solution and 40% by mass of acrylamide aqueous solution, stir evenly, then add 3% by mass of sodium alginate aqueous solution, 0.5 M calcium sulfate dihydrate and 0.05 M α-ketoglutaric acid to mix well to obtain a hydrogel matrix layer precursor solution. Pour the precursor solution into a mold and place it in a dark box. Irradiate with 365 nm ultraviolet light for 10 minutes to form a gel to obtain a hydrogel matrix layer.

[0032] (2) Preparation of adhesive layer powder: Mix 3% silk fibroin solution and 3% polyethylene glycol aqueous solution in a volume ratio of 3:1, then add an equal volume of 30% tannic acid aqueous solution and mix well. Discard the liquid portion, freeze-dry the solid colloidal substance at -80°C, grind it, and sieve it through a 200-mesh sieve to obtain the adhesive layer powder.

[0033] (3) Preparation of silk fibroin-based adhesive patch: The adhesive layer powder prepared above is coated on the hydrogel matrix layer, and the temperature of the constant temperature and humidity incubator is set to 35°C and the relative humidity is set to 50%. After standing for 2 minutes, a silk fibroin-based adhesive patch is obtained.

[0034] The tensile elongation of the adhesive patch in this embodiment is 280%, and the toughness strength is 510 KJ / m 3 The adhesion strength in the blood environment is 712.56 J / m 2 .

[0035] Example 5 This embodiment discloses a method for preparing a silk fibroin-based adhesive patch for sutureless repair of tissue trauma, and the specific steps are as follows (1) Preparation of hydrogel matrix layer: Mix 3% by mass methacrylate-modified silk fibroin solution and 20% by mass acrylamide aqueous solution, stir evenly, then add 4% by mass sodium alginate aqueous solution, 0.8 M calcium sulfate dihydrate and 0.065 M α-ketoglutaric acid to mix well to obtain a hydrogel matrix layer precursor solution. Pour the precursor solution into a mold and place it in a dark box. Irradiate with 365 nm ultraviolet light for 10 minutes to form a gel to obtain a hydrogel matrix layer.

[0036] (2) Preparation of adhesive layer powder: Mix 7% silk fibroin solution and 4% polyethylene glycol aqueous solution in a volume ratio of 1:5, then add an equal volume of 10% tannic acid aqueous solution and mix well. Discard the liquid portion, freeze-dry the solid colloidal substance at -80°C, grind it, and sieve it through a 200-mesh sieve to obtain the adhesive layer powder.

[0037] (3) Preparation of silk fibroin-based adhesive patch: The adhesive layer powder prepared above is coated on the hydrogel matrix layer, and the temperature of the constant temperature and humidity incubator is set to 38°C and the relative humidity is set to 60%. After 18 minutes, the silk fibroin-based adhesive patch can be obtained.

[0038] The tensile elongation of the adhesive patch in this embodiment is 320%, and the toughness strength is 580 KJ / m 3 The adhesion strength in the blood environment is 771.89 J / m 2 .

[0039] Comparative Example 1 This comparative example discloses a method for preparing a silk fibroin-based adhesive patch for sutureless repair of tissue trauma, and the specific steps are as follows (1) Preparation of hydrogel matrix layer: Mix 1% methacrylate-modified silk fibroin solution and 30% acrylamide aqueous solution together, then add 2% sodium alginate aqueous solution, 0.75 M calcium sulfate dihydrate and 0.075 M α-ketoglutaric acid to obtain a hydrogel matrix layer precursor solution. Pour the precursor solution into a mold and place it in a dark box. Irradiate with 365 nm ultraviolet light for 10 minutes to form a gel to obtain a hydrogel matrix layer.

[0040] (2) Preparation of adhesive layer colloid: Mix 5% silk fibroin solution and 2% polyethylene glycol aqueous solution in a volume ratio of 1:1, then add an equal volume of 20% tannic acid aqueous solution and mix well. Discard the liquid part and leave the solid colloid.

[0041] (3) Preparation of silk fibroin-based adhesive patch: The solid colloidal substance prepared above is coated on the hydrogel matrix layer, and a constant temperature and humidity incubator is set at 37°C and relative humidity at 60% for 5 minutes to obtain a silk fibroin-based adhesive patch.

[0042] The tensile elongation of the adhesive patch prepared in this comparative example is 60%, and the toughness strength is 78 KJ / m 3 The adhesion strength in the blood environment is 60.79 J / m 2 , which is much lower than the adhesive patch prepared in Example 3.

[0043] Because the solid colloidal substance cannot diffuse and penetrate on the surface and inside of the hydrogel matrix layer, the contact and bonding surface between the two is not tight enough, and the two-layer structure of the patch obtained is poorly fitted, causing the solid colloidal substance and the hydrogel matrix layer to be easily separated during the stretching process, and the patch performance is poor. Compared with Example 3, the use of adhesive layer powder is more conducive to the close combination of the hydrogel matrix layer and the adhesive layer, and the adhesive layer powder absorbs moisture and fuses, and it diffuses and penetrates uniformly on the surface and inside of the gel matrix layer, which is more conducive to its close combination with the hydrogel matrix layer. Compared with the coating of the solid colloidal substance using the preparation method step alone, the two-layer structure of the patch obtained by using the adhesive layer powder to be coated on the hydrogel matrix layer is more closely fitted, and the performance is more uniform. The characteristics of in-situ fusion and penetration after the adhesive layer powder absorbs moisture play an important role in the excellent performance of the patch material of the present invention, and the in-situ bonding effect is better.

[0044] The above descriptions are merely embodiments of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention shall fall within the scope of the present invention.

Claims

1. A method for preparing a silk fibroin-based adhesive patch for sutureless repair of tissue trauma, characterized in that: The patch consists of two layers. The first layer is a hydrogel matrix layer formed by cross-linking methacrylated silk protein with acrylamide, and adding sodium alginate and calcium ions; the second layer is a bonding layer formed by self-assembly cross-linking of silk protein, polyethylene glycol and tannic acid.

2. The method for preparing a silk fibroin-based adhesive patch for sutureless repair of tissue trauma according to claim 1, characterized in that: The specific steps include: (1) Preparation of hydrogel matrix layer: Add acrylamide aqueous solution to the methacrylated silk fibroin solution and stir evenly, then add sodium alginate aqueous solution, calcium sulfate dihydrate and photoinitiator and mix well to obtain a hydrogel matrix layer precursor solution, pour the precursor solution into a mold and place it in a dark box, and irradiate with ultraviolet light for 10 minutes to form a hydrogel matrix layer; (2) Preparation of adhesive layer powder: The silk fibroin solution and the polyethylene glycol aqueous solution are mixed, and an equal volume of tannic acid aqueous solution is added, and stirred to obtain a solid colloidal substance. The solid colloidal substance is freeze-dried, ground, and sieved to obtain an adhesive layer powder; (3) Preparation of a silk fibroin-based adhesive patch: coating the adhesive layer powder obtained in step (2) on the hydrogel matrix layer obtained in step (1), and placing the mixture in a constant temperature and humidity incubator to obtain a silk fibroin-based adhesive patch; the temperature in the constant temperature and humidity incubator is 35°C-38°C, and the relative humidity is 50%-60%.

3. The method for preparing a silk fibroin-based adhesive patch for sutureless repair of tissue trauma according to claim 2, characterized in that: The preparation method of the methacrylated silk fibroin solution in step (1) is to dissolve the degummed silk with lithium bromide to obtain a silk fibroin solution, then add glycidyl methacrylate, stir for 3 hours in a dark place, then dialyze with deionized water for 5-7 days, centrifuge, and take the supernatant to obtain a methacrylated silk fibroin solution, wherein the mass fraction of the methacrylated silk fibroin solution is 0.1% - 5%.

4. The method for preparing a silk fibroin-based adhesive patch material for sutureless repair of tissue trauma according to claim 2, characterized in that: In step (1), the mass fraction of the acrylamide aqueous solution is 10%-50%, the mass fraction of the sodium alginate aqueous solution is 1%-5%, the molar concentration of the calcium sulfate dihydrate is 0.1M-1M; and the molar concentration of the photoinitiator is 0.001M-0.1M.

5. The method for preparing a silk fibroin-based adhesive patch material for sutureless repair of tissue trauma according to claim 2, characterized in that: The photoinitiator described in step (1) is lithium phenyl-2,4,6-trimethylbenzoylphosphinate or α-ketoglutaric acid.

6. The method for preparing a silk fibroin-based adhesive patch material for sutureless repair of tissue trauma according to claim 2, characterized in that: The preparation method of the silk fibroin solution in step (2) is to dissolve the degummed silk with lithium bromide, then dialyze with deionized water for 1-3 days, and centrifuge to obtain the silk fibroin solution; the mass fraction of the silk fibroin solution is 1%-10%.

7. The method for preparing a silk fibroin-based adhesive patch material for sutureless repair of tissue trauma according to claim 2, characterized in that: The polyethylene glycol in step (2) is one of polyethylene glycol 500, polyethylene glycol 1000 and polyethylene glycol 2000; the mass fraction of the polyethylene glycol aqueous solution is 1%-5%.

8. The method for preparing a silk fibroin-based adhesive patch material for sutureless repair of tissue trauma according to claim 2, characterized in that: In step (2), the volume ratio of the silk fibroin solution to the polyethylene glycol aqueous solution is 5:1-1:5; the mass fraction of the tannic acid aqueous solution is 10%-30%.

9. The method for preparing a silk fibroin-based adhesive patch material for sutureless repair of tissue trauma according to claim 2, characterized in that: The standing time in step (3) is 1-20 minutes.

10. A silk fibroin-based adhesive patch for sutureless repair of tissue trauma prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Composite biological material patch and preparation method thereof

    CN103908692A

  • Polyphenol-silk fibroin-polyethylene glycol medical tissue adhesive as well as preparation method and application thereof

    CN114344556A

  • Photo-crosslinking silk fibroin hemostatic adhesive and preparation method thereof

    CN115636960A

  • Microneedle adhesive patch based on hydrogel formulation

    WO2019221559A1